2010
DOI: 10.4049/jimmunol.1000387
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein-A Inhibits Mycoplasma-Induced Dendritic Cell Maturation through Regulation of HMGB-1 Cytokine Activity

Abstract: During pulmonary infections, a careful balance between activation of protective host defense mechanisms and potentially injurious inflammatory processes must be maintained. Surfactant protein A (SP-A) is an immune modulator that increases pathogen uptake and clearance by phagocytes while minimizing lung inflammation by limiting dendritic cell (DC) and T cell activation. Recent publications have shown that SP-A binds to and is bacteriostatic for Mycoplasma pneumoniae (Mp) in vitro. In vivo, SP-A aids in mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In previous studies using WT and SP-A −/− mice, we have shown that SP-A is protective against live Mp infection (23). Since SP-A binds Mp and acts as an opsonin, we sought to determine if the phenotypes observed in Mp-infected SP-A −/− mice were due to the increased pathogen burden, or innate recognition of pathogen-derived material.…”
Section: Introductionmentioning
confidence: 88%
“…In previous studies using WT and SP-A −/− mice, we have shown that SP-A is protective against live Mp infection (23). Since SP-A binds Mp and acts as an opsonin, we sought to determine if the phenotypes observed in Mp-infected SP-A −/− mice were due to the increased pathogen burden, or innate recognition of pathogen-derived material.…”
Section: Introductionmentioning
confidence: 88%
“…Surfactant proteins, SP-A and SP-D, are found in serous cells (334,568) and kill bacteria by permeabilizing their membranes (750). SP-A is also an immune modulator (373).…”
Section: Proteins Peptides and Small Organic Moleculesmentioning
confidence: 99%
“…All three have been shown to be protective in models of acute inflammation . Both monoclonal and polyclonal antibodies that directly bind to HMGB1 as well as the small molecule glycyrrhizin, which binds to HMGB1 with high affinity, were broadly protective in experimental models of inflammation . Recombinant A box was antagonistic to B box and full‐length HMGB1 and is thought to compete with HMGB1 for receptor activation .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%